The prevalence and burden of interstitial lung diseases in the USA - Jeganathan, Niranjan; Sathananthan, Matheni (ERJ open research, 2022)
Interstitial lung diseases (ILDs) are a significant contributor to disability and deaths in the USA. The prevalence and deaths from ILDs have increased but when adjusted for age, have been stable since 2010. https://bit.ly/3IDlZrg.Interstitial lung diseases (ILDs) are a significant contributor to disability and deaths in the USA. The prevalence and deaths from ILDs have increased but when adjusted for age, have been stable since 2010. https://bit.ly/3IDlZrg.